Reducing sample size requirements for future ALS clinical trials with a dedicated electrical impedance myography system. Issue 7 (2nd October 2018) - Shefner, Jeremy M.; Rutkove, Seward B.; Caress, James B.; Benatar, Michael; David, William S.; Cartwright, Michael S.; Macklin, Eric A.; Bohorquez, Jose L.
Abstract: Objective: In this longitudinal multicenter cohort study, we evaluated the potential of a dedicated electrical impedance myography (EIM) device to assess ALS progression and the system's basic reproducibility and diagnostic accuracy. Methods: Forty-six ALS patients underwent up to five sequential measurements of multiple muscles over a period of 8 months at 2-month intervals using the mView EIM device (Myolex, Inc., San Francisco, CA). Standard measures of disease status were also obtained. A group of 30 healthy volunteers and 30 ALS-mimics were evaluated once to determine if the technique could assist with initial diagnosis. Several electrode arrays and EIM outcomes were assessed. Results: EIM tracked ALS progression; power analyses suggested a 5.2-fold reduction in sample size requirements compared to ALSFRS-R by utilizing 50 kHz phase value from the muscle with the greatest EIM decline in each subject. This progression rate correlated to total ALSFRS-R progression, with R = 0.371, p = 0.021. Reproducibility was high, with both intra- and inter-rater intraclass correlation coefficients for individual muscles mostly greater than 0.90. The mean 50 kHz phase distinguished between ALS patients and healthy controls (area-under-curve 0.78, 95% confidence intervals (CIs) 0.68, 0.89), but not between mimics and ALS patients (area-under-curve 0.60, 95% CIs 0.47, 0.73). Conclusions: While limited in its specificity to identify ALS versus disease mimics, these results support the hypothesis that single-muscle EIM can serve as a convenient, repeatable, and powerful outcome measure in ALS clinical trials.